Unveiling excited state energy transfer and charge transfer in a host/guest coordination cage. Issue 4 (21st December 2017) - Zhang, Rui-Ling; Yang, Yang; Yang, Song-Qiu; Han, Ke-Li
Abstract : Ultrafast excited-state dynamic processes, charge and energy transfer in a HGCT system are unveiled by using femtosecond transient absorption spectroscopy. Abstract : Host–guest charge transfer (HGCT) plays a key role in applications from solar energy conversion to photocatalysis. Herein, a HGCT system, a pillared Pt(ii ) metallacage with encapsulated coronene was synthesized and the ultrafast excited-state dynamics were investigated by combination of femtosecond transient absorption spectroscopy, nanosecond transient emission spectrocopy and quantum chemistry calculations. Two significant ultrafast dynamic processes were unveiled: (i) charge transfer from a singlet local excited ( 1 LE) state associated with the coronene moiety to a 1 HGCT state with τ = 9.5 ps; and (ii) triplet–triplet energy transfer from a high 3 HGCT state to a 3 LE state with τ = 139.5 ps. The resulting long-lived species, the lowest 3 LE and 3 HGCT states eventually decay to the ground state in microsecond time scales of 5.2 and 43.4 μs respectively. Moreover, a clear mechanism depicting the main excited-state decay pathways connecting the initial photoexcited transients with the resulting species was proposed.